1990
DOI: 10.1063/1.103176
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in misfit dislocation density by the selective growth of Si1−xGex/Si in small areas

Abstract: Si1−xGex and Si layers have been grown selectively in the exposed Si regions on oxide-patterned 〈100〉 oriented Si wafers using the chemical vapor deposition technique limited reaction processing. Misfit dislocation spacings at the heterointerface were measured using plan-view transmission electron microscopy in conjunction with a large-area thinning technique which allows for examination of 100–150 μm diameter areas. The dislocation density is reduced by at least a factor of 20 for small areas (lateral dimensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(32 citation statements)
references
References 10 publications
3
29
0
Order By: Relevance
“…Shown in Fig. 6 is an atomic force micrograph of GaAs deposited into 2.0-mm-wide trenches spaced apart by 16 Fig. 8.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Shown in Fig. 6 is an atomic force micrograph of GaAs deposited into 2.0-mm-wide trenches spaced apart by 16 Fig. 8.…”
Section: Resultsmentioning
confidence: 99%
“…However, the thick buffer layer can be time and materials intensive, and thermal annealing might harm previously deposited Si devices. An alternative approach to reducing the dislocation density is to decrease the epitaxial area with an inert mask [16][17][18][19]. This method, known as selective area epitaxy (SAE), has been shown to extend the critical thickness of heteroepitaxial growth [17].…”
Section: Introductionmentioning
confidence: 99%
“…Growth on isolated mesas allows threading dislocations propagating through the layer to reach mesa boundaries and exit the mesa surface. Similar techniques have been applied successfully to other materials systems, including GaAs on Si, 2,3 In x Ga 1Àx As on GaAs, 4,5 Si x Ge 1Àx on Si, [5][6][7][8][9] ZnSe on GaAs, 10,11 and Hg x Cd 1Àx Te on Zn x Cd 1Àx Te. 12 For these systems, a combination of annealing to set dislocations into motion and the proximity of mesa sidewalls that act as dislocation sinks has resulted in a reduction in dislocation density at the top of the mesas.…”
Section: Introductionmentioning
confidence: 92%
“…Another approach is to use a patterned substrate with reduced seed layer dimensions [5]. It was shown that misfit dislocation density was reduced by a factor of 20 by using finger-type oxide isolation [6]. Threading dislocation density was also lowered by one order of magnitude (to 10 6 cm À2 ) by using two-dimensional oxide pillar arrays [7].…”
Section: Introductionmentioning
confidence: 98%